Evaluating a motivational and psycho-educational self-help intervention for athletes with mild eating disorder symptoms: A mixed methods feasibility study - Sebastian Schanche Sandgren; Emma Haycraft; Jon Arcelus; Carolyn Plateau (2022)
Objective: The primary aim was to assess the feasibility of undertaking a study evaluating the novel Motivational and Psycho-Educational Self-Help Programme for Athletes with Mild Eating Disorder Symptoms (MOPED-A). A mixed-methods approach was adopted to explore the feasibility of recruiting and retaining participants, and to evaluate the acceptability of measures, procedures and the intervention. A secondary aim was to explore the potential efficacy of MOPED-A in reducing athletes’ eating disorder symptoms. Method: Thirty-five athletes were recruited. Participation involved completing MOPED-A over 6-weeks and completing self-report measures at baseline (T1), post-intervention (T2) and 4-week follow-up (T3). A subsample (n=15) completed an interview at T2. Results: Retention was good throughout the study (n=28; 80%). Quantitative and qualitative feedback suggested the format, delivery, content and dosage of MOPED-A were acceptable. Athletes valued that the intervention was tailored to them, and this facilitated both participation and completion. Over a third of participants reported disclosing their eating difficulties and deciding to seek further support. Large reductions in eating disorder symptoms were detected at T2 and sustained at T3. Conclusions: The MOPED-A intervention can be feasibly implemented, is acceptable to participants, and demonstrates potential for reducing symptoms in athletes. A larger, controlled trial is warranted.